ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA PADA MATERI BILANGAN BULAT - Jumrawarsi Jumrawarsi (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2021)
The purpose of this study was to determine the high order thinking skills of class VII.1 SMPN 4 Pariaman students on integer material. This research is a qualitative descriptive study. The research subjects consisted of 6 grade VII.1 students consisting of 2 high-ability, 2 moderate and 2 low-level students based on the value of assignments and daily tests of integer material and considerations of the mathematics teacher. Data analysis was in the form of analysis of students' test abilities, analysis ability in aspects of knowledge according to Bloom Taxonomy and interview analysis. The data validity test was done by using triangulation technique. The results of the test research show that the Bloom Taxonomic percentage of the increase with the average Bloom Taxonomy level of C4, C5, and C6 is 87.21%, 70.27%, 57.91%, respectively. This is the ability students have in solving problems that require higher-order thinking skills.